To find the equation of the function, we use
![y=a(x-h)^2+k](https://img.qammunity.org/2023/formulas/mathematics/college/97p0xsjs0cwme4ddvwkim2cbbqprhnlhsv.png)
(h,k) is the vertex
Then, we we replace the values and find the value of "a"
![\begin{gathered} y=a(x-6)^2+4 \\ (12,0) \\ 0=a(0-6)^2+4 \\ a=-(4)/((-6)^2)=-(1)/(9) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7bpvwzlcvb5iuuv522b670ls4yofwjcg0a.png)
Finally, the equation is,
![y=(1)/(9)(x-6)^2+4](https://img.qammunity.org/2023/formulas/mathematics/college/73hl2t745hygz19g5e5of42tlqizc2cdh7.png)
Subtitute 6 for h and 4 for k into the vertex form of a quadratic function: y = a(x-6)^2+4
Then substitute 0 for x and 0 for y and solve for a:a=-1/9